Community Center of Campinas: a look to the architecture of Fábio Penteado - Trevisan, Ricardo (Risco - Journal of Architecture and Urbanism, 2010)
A center for socializing, a living for the masses. Thus is revealed the Cultural Community Center of Campinas (CCC), particular work of architect Fábio Penteado (FP), the object of analysis and study of this article. Situated in the city of Campinas, it history takes us to the cultural history of this city, as well as the professional history of FP. Architect with extensive practice and theory production, who synthesized at CCC concepts imagined and applied in other works. Designed in 1968, this equipment has become an architectural landmark for Campinas. But would this mark a constraint strong enough to ensure his brilliance as a public building?